Ossificação da sutura palatina mediana após o procedimento de expansão rápida da maxila: Estudo radiográfico - Filho, Omar Gabriels da Silva; Graziani, Guilherme Fernandes; Lauris, Rita de Cássia Moura Cervalho; Lara, Tulio Silva [UNESP] (FapUNIFESP (SciELO), 2008)
Objective: the current study aims at following up radiographically the evolution of the midpalatal suture during the expansion procedure since the opening of the suture until bone formation. Methods: the sample comprised 38 patients in the mixed dentition stage submitted to the rapid palatal expansion protocol of the Hospital for Rehabilitation of Craniofacial Anomalies. Results: it was observed an individual variation on the period of bone ossification of the midpalatal suture, which justifies the radiographic follow-up as determinant for the appliance removal. Due to long-term post-treatment stability, the expander should be removed after the new suture is completely formed. Conclusions: the findings show that it is necessary more than three months for the complete reorganization of the midpalatal suture during the passive phase of the rapid palatal expansion.
Midpalatal suture ossification post rapid palatal expansion: A radiographic study
Keywords: Diagnostic imaging; Orthodontics; Rapidly maxillary expansion; Suture